Zhong Hui’s Laozi commentary and the debate on capacity and nature in third-century China - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2003)
Zhong Hui (a.d. 225-264) was a major, albeit neglected figure in third-century Chinese intellectual history. Author of a Laozi com mentary, a work on the relationship between "capacity" (cai yf) and "nature" (xing f-fe), two treatises on the Yijing HH, and other writings, Zhong Hui played a significant role in the development of xuanxue -P (learning of the mysterious Dao), which, as is well known, came into prominence during the Zhengshi JEin reign (240-249) of the Wei H dy nasty (220-265) and dominated the Chinese intellectual scene well into the sixth century Zhong Hui was highly regarded by his contemporaries and rivaled Wang Bi JIWj (226-249) as one of the brightest "stars" among the cultural and political elite. Politically, Zhong was, in fact, a far more important figure than Wang Bi. Political ambition, however, exacted a heavy price—at the end of a successful military campaign against the kingdom of Shu Sri, Zhong Hui attempted to march against the ruling Sima W] J§ regime itself, which cost him his life.